2002
DOI: 10.1248/bpb.25.1289
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Administration of Hypericum perforatum Improves Spatial Learning and Memory in the Water Maze.

Abstract: The aim of the present study is to investigate the effects of long-term Hypericum perforatum treatment on spatial learning and memory in rats. Hypericum preparation (HP) standardized to 0.3% hypericin content was administered orally for 9 weeks in doses of 4.3 and 13 m mg/kg corresponding to therapeutic dosages in humans of 0.3 and 0.9 mg of total hypericins daily. A Morris water maze paradigm was used. The mean escape latency over 4 d for the Control group (21.9 s) and HP 4.3 group (21.7 s) was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Additionally, IHp showed antidepressant, anxiolytic, antiamnestic, antiinflammatory and analgesic and antistress activities in various animal models 2000a;2000b;2001a;2001b;Zhang, 2004). Some researchers recently found that HP had neuroprotective effects and diminished cognitive impairment and improved spatial learning and memory (Trofimiuk et al, 2005;Silva et al, 2004;Kumar et al, 2003;Widy-Tyszkiewicz et al, 2002;Kumar et al, 2002;Klusa et al, 2001;Kumar et al, 2000c). Other studies confirmed that hyperforin released hippocampal acetylcholine (Kiewert et al, 2004;Buchholzer et al, 2002) and HP reduced the degradation rate of acetylcholine (Re et al, 2003).…”
Section: Hypericum Perforatum (St John's Wort)mentioning
confidence: 95%
“…Additionally, IHp showed antidepressant, anxiolytic, antiamnestic, antiinflammatory and analgesic and antistress activities in various animal models 2000a;2000b;2001a;2001b;Zhang, 2004). Some researchers recently found that HP had neuroprotective effects and diminished cognitive impairment and improved spatial learning and memory (Trofimiuk et al, 2005;Silva et al, 2004;Kumar et al, 2003;Widy-Tyszkiewicz et al, 2002;Kumar et al, 2002;Klusa et al, 2001;Kumar et al, 2000c). Other studies confirmed that hyperforin released hippocampal acetylcholine (Kiewert et al, 2004;Buchholzer et al, 2002) and HP reduced the degradation rate of acetylcholine (Re et al, 2003).…”
Section: Hypericum Perforatum (St John's Wort)mentioning
confidence: 95%
“…in the volume of 1.5 mL/kg. This dose corresponds to the human recommended daily dose of 2.8 mg total hypericins (Widy-Tyszkiewicz et al, 2002;Kemper, 2003).…”
Section: Drugsmentioning
confidence: 99%
“…A number of studies have shown that Hypericum perforatum extract has memory enhancing properties in rodents (Khalifa, 2001; Klusa et al ., 2001, Kumar et al ., 2000). Long term administration of Hypericum perforatum also improves learning and spatial memory of the treated rats (Widy‐Tyszkiewicz et al ., 2002). Another study indicates anxiolytic and antipanic effects of H. perforatum extract on rats tested in the elevated T‐maze (Beijamini and Andreatini, 2003).…”
Section: Introductionmentioning
confidence: 99%